BrRAV8 negatively modulates thermotolerance through suppressing cellulose biosynthesis in flowering Chinese cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) - Lu, Dalian (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.